The hummingbird effect [videorecording (DVD)] - Shultz, Doug; Shum, Harry, Jr., 1982- (PBS Distribution, 2023)
Costa Rica's motto is Pura Vida, Pure Life, and this deceptively small country is bursting with some of the most spectacular wildlife and pristine ecosystems in the world. All this diversity thrives, in part, thanks to one surprising little creature: hummingbirds. Venture across Costa Rica's wild and rugged landscapes, from volcanic peaks to coastal jungle to misty cloud forests and discover the nation's dazzling diversity of hummingbirds. Watch how these tiny birds play an outsize role in maintaining some of the richest and wildest environments on Earth, where a whole community of creatures, such as macaws and monkeys, enjoys The Hummingbird Effect.